Associations between Waist Circumference and Sex Steroid Hormones in US Adult Men: Cross-Sectional Findings from the NHANES 2013–2016 - Zhisheng Zhu; Xingong Lin; Chaoyang Wang; Shize Zhu; Xianying Zhou (International Journal of Endocrinology)
Background. Obesity is recognized as a major public health issue worldwide, characterized by a growing prevalence among adult males. Several studies have identified an association between obesity and sex steroid hormone levels but only a few have considered the relationship between waist circumference (WC) and sex hormone levels in adult males. This study therefore aimed to evaluate the relationships between waist circumference (WC) and various sex steroid hormone levels in adult males in the United States. Methods. This study analyzed data from 3,359 adult males aged 20 years and above, who participated in the National Health and Nutrition Examination Survey (NHANES) from 2013–2016 in the United States. We collected demographic data, including WC, and serum levels of testosterone, estradiol, SHBG, FAI, and T/E2 ratio. We adjusted the variables using multiple linear regression models with R 4.2.2 and EmpowerStats. Results. After adjusting for confounders, WC was found to be negatively associated with testosterone (β = −0.117, P<0.001) but positively correlated with estradiol (β = 0.002, P=0.002), especially beyond a WC of 104.5 cm (β = 0.004, P<0.001). Underweight individuals showed a contrasting positive correlation between WC and testosterone (β = 0.351, P=0.016). WC was inversely related to SHBG, particularly when WC was ≤99.1 cm (β = −0.036, P<0.001). The FAI initially increased and then decreased with WC, peaking at 98.6 cm. The T/E2 ratio negatively correlated with WC (β = −0.074, P<0.001). These relationships varied among subgroups but remained unaffected by age or physical activity time. Conclusions. Waist circumference is inversely correlated with testosterone, SHBG, and T/E2 ratio but positively correlated with estradiol, except for a positive correlation with testosterone in underweight males. Waist circumference serves as a crucial anthropometric measurement indicator for predicting sex steroid hormone levels in adult males.